Relationship of historical copper mining to the transport and accumulation of trace metals and salts in semi-arid environments : an example from Buffels River, Northern Cape, South Africa - Dunford, Alexander (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.